Characterization of polysaccharides isolated from gums of two venezuelan specimens of Albizia niopoides var. colombiana - León de Pinto, Gladys; Martínez, Maritza; Beltrán, Olga; Rincón, Fernando; Clamens, Carmen; Igartuburu, José Manuel; Guerrero, Rocio; Vera, Antonio (Ciencia)
The genus Albizia durazzini comprises 150 species; some of these species are disseminated in Venezuela. Albizia niopoides var. colombiana exudes a clear gum, very soluble in cold water at room temperature. Analytical data of the gum exudates from two specimens of that species showed little variation. The polysaccharide isolated from de gums contains galactose, arabinose, rhamnose, glucuronic acid and its 4-0-methyl derivative. The high content of rhamnose is comparable to that reported for A. forbessi. It was not detected mannose. Although, the presence of this sugar in most of Albizia gums has been taken as a feature of great diagnostic significance. The analytical data reported in this work is a contribution to augment the data existing for the gums from Albizia spp. The NMR spectra of the polysaccharides studied showed many interesting structural features which are according to the analytical data.